Evaluasi Penyebab Genangan Banjir Wilayah Perkotaan Pringsewu Berdasarkan Dimensi Saluran Drainase Eksisting - Ismadi Raharjo (Jurnal Ilmiah Teknik Pertanian - TekTan, 2014)
Subdistrict Pringsewu consisting of 13 villages are urban area that is now the capital of the district Pringsewu. For urban areas, sub Pringsewu require well drainage infrastructure. In fact, today, if heavy rains, there are several locations, especially in the national road (Jalan Ahmad Yani) and provincial road (Jalan KH Gholib) were flooding  . This study aimed to evaluate the cause of the flooding in  urban areas Pringsewu based on the dimensions of the existing drainage channel. The research was conducted from June to December 2013. The results of the observation pattern Pringgsewu flow direction in the region can be divided into two (2) primary drainage systems, Sidoarjo System and Way Semah System. Rate of region rain through Thiesen polygon from 3 (three) rain stations that are representative of the region and then analyzed using the method Log Person III and Gumbel with return period of 50 years gain Rainfall of maximum daily (RH max) of 110,81 mm/h. Maxiimal rain intensity (I max) with a return period of 50 years using the formula obtained Mononobe is 13,03 mm./h. Drainage coefficient value (C)   is influenced by the use of land that is currently changing in urban areas Pringsewu, Sidoarjo system is expected to have a value of C=0,65, and for systems Way Semah estimated to have a value of C=0,45. With variable of I max and C as well as the value of the catchment area (A) which depends on each zone served by drainage channels, then by using the rational formula can be calculated discharge runoff that is expected to flow into the drainage channel at Q=CIA. From measurement of the existing dimensions of the drainage channel can be estimated the capacity of the channel, so as to evaluate the adequacy the drainage channel capacity to accommodate the runoff discharge in each zone. The results of these evaluations is only about 15,3% of channels in Sidoarjo system sufficient; whereas in the system Way Semah about 20%. For that in order to address the problem of flooding urban areas Pringsewu need immediate revitalization of existing drainage channel dimensions so that  the channels have sufficient capacity to accommodate rainfall runoff discharge in each zone. Keywords: flooding, urban areas, capacity drainage channel, discharge run off